NEW OPPORTUNITIES FOR STUDYING THE FUNCTION OF EXTERNAL RESPIRATORY IN CHILDREN - Tashmatova, Gulnoza (Medical science of Uzbekistan, 2025)
This article is devoted to such a topical problem of social medicine as asthma and allergy in children, which has important theoretical and practical significance. The aim of the work is to evaluate the diagnostic capabilities of modern methods for studying the function of external respiration in children with exacerbation of bronchial asthma. Materials and methods. We observed 220 children with bronchial asthma aged from 2 to 16 years. Depending on the severity of the course, all children were divided into two groups: 140 children with intermittent, 80 children - with mild persistent course of the disease. The control group consisted of 23 practically healthy children of the same age. Of the functional tests, spirometry was carried out on the Microlab device (England). The assessment of the parameters of the forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC) and the FEV1 / FVC ratio was carried out after the test with a bronchodilator (DAI Salbutamol, 200 mcg). For a more in-depth examination, body plethysmography was performed using the Master Screen Body device (Jaeger, Germany). Statistical analysis was performed using the STATISTICA 10 program. Results and discussion. In all children with bronchial asthma, difficulty breathing occurred mainly at night. In addition, 82.3% of children often recorded attack equivalents (a feeling of shortness of breath, dry paroxysmal cough), which recurred 1-3 times a month, lasting from 5-10 minutes, difficulty breathing was relieved on its own or after a single use of bronchodilators. The FEV1 value in children with bronchial asthma was 92.4%, in children of the control group 100.2%. When analyzing the FEV1/FVC indicator, which characterizes the presence of bronchial obstruction, it was found that in the group of children with bronchial asthma it was 69.6%, while in the control group it was 97.53%. When conducting spirography in children with bronchial asthma after inhalation of 200 mcg salbutamol, the FEV1 level was 101.2% and was comparable with the values ​​​​of children in the control group. The FEV2 / FVC indicator was within the normal range and was 70.3% in the group of children with bronchial asthma and 95.2% in the group of "conditionally healthy" children. Conclusions. Given the above data, it can be concluded that in children with controlled bronchial asthma, obstructive disorders are not detected when determining lung function by spirography, although the FEV1 and FEV1 / FVC indicators are statistically lower than in the group of healthy children. A reliable increase in OLV is revealed relative to the control group. Based on this, a more in-depth examination, in particular, body plethysmography, is required to clarify the presence of external respiration disorders and pathology of small bronchi in children with bronchial asthma.